血液学的毒性バイオマーカーとしてのＧＤＦ−１５ (2018)
本開示は、Ｍｄｍ２阻害剤の毒物学的作用を判定するための安全性バイオマーカーとしてのＧＤＦ−１５の使用、対象におけるＭｄｍ２阻害剤の毒物学的作用を判定するための、特にある用量のＭｄｍ２阻害剤の投与に応答して対象において血小板減少症の発症の可能性を判定するためのｅｘ ｖｉｖｏ方法、対象におけるがんの処置においてＭｄｍ２阻害剤を使用する方法、がんを有する患者が、ある用量のＭｄｍ２阻害剤を用いる処置に応答して血小板減少症を発症する可能性を予測する際に使用するためのキット、がんを有する患者を処置する際に使用するためのキットおよび関連する開示実施形態に関する。 The present disclosure relates to use of GDF-15 as a safety biomarker for determining a toxicological effect of a Mdm2 inhibitor; an ex vivo method for determining a toxicological effect of a Mdm2 inhibitor in a subject, in particular for determining a likelihood of developing thrombocytopenia in a subject in response to administration of a dose of a Mdm2 inhibitor; methods of using a Mdm2 inhibitor in the treatment of cancer in a subject; a kit for use in predicting the likelihood that a patient having cancer will develop thrombocytopenia in response to a treatment with a dose of a Mdm2 inhibitor; a kit for use in treating a patient having cancer and related disclosure embodiments.